Les hôpitaux de Rennes : histoire, architecture et patrimoine - Capucine Lemaître; Benjamin Sabatier (In Situ)
The hospital heritage of the city of Rennes illustrates the new directions in which health services developed during the nineteenth and twentieth centuries, and the unsettled political circumstances of that time. Two important hospital groups were erected in the nineteenth century and subsequently witnessed substantial improvements. The first, the Hôtel-Dieu, was built, after a competition in 1858, by Aristide Tourneux. Located to the north of the city, near the historical centre, it was the first modern hospital of Rennes. The Pontchaillou hospital, to the north-west of the city, designed by Julien Ballé in 1895, was first a hospice before focusing on more important services, at the expense of the initial ones. Signs of these changes were perceptible in the 1930s with Eugène Marquis’s anti-cancer centre and were confirmed in the 1950s with its new denomination as a university-affiliated hospital. The Pontchaillou site is now the main hospital for Rennes and is of regional significance, due to the construction of its blood transfusion centre and its heart and pneumology centre. The Hôtel-Dieu, on the other hand, now only hosts a service for elderly people. Part of the estate is currently being developed for housing, but the original building is an empty shell with an uncertain future.